The Comparative of Indonesian and Western Culture in Live Action: A Study of Cross-Culture - Bambang Nur Alamsyah Lubis; Rakhmat Wahyudin Sagala (English Teaching and Linguistics Journal (ETLiJ), 2020)
This study deals with cross-culture of people who live in Indonesia and western. Especially, the national culture of Indonesia that is going to compare with western culture. People know that every country has its own culture, the eastern and western countries have their way of going live. The aim of this study is to compare the culture of Indonesia and western people in their daily live. This study used descriptive qualitative method. This study analysed the utterances, actions and the way of life Indonesia and western people. The result, there are many significant different ways of life, utterance, and action that actually allowed in Indonesia but forbidden in western people.